2021
DOI: 10.3390/d13110579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Autonomous Reef Monitoring Structures (ARMS) for Describing the Species Diversity of Two Coral Reefs in the Yucatan Peninsula, Mexico

Abstract: Autonomous reef monitoring structures (ARMS) have been proposed as a standardized, passive, nondestructive sampling tool. This study assessed the ability of ARMS to capture the cryptic species diversity of two coral reefs by recording species richness and taxonomic representativeness using conventional taxonomy. The capacity of ARMS, as artificial substrates, to favor the establishment of nonindigenous species over native species was also evaluated. The use of ARMS allowed the detection of 370 species morphoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The majority of non‐metazoan eukaryote taxa are small and difficult to sample. ARMS becomes advantageous as it provides an efficient method to collect, study and characterize such communities (Casey et al, 2021; Palomino‐Alvarez et al, 2021; Pearman et al, 2019, 2020). Here, we identified marine fungi Ascomycota, Basidiomycota, and red algae Rhodophyta as the main non‐metazoan eukaryote contributors to a tropical urban reef cryptobiome (Figure 2b; Appendix S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of non‐metazoan eukaryote taxa are small and difficult to sample. ARMS becomes advantageous as it provides an efficient method to collect, study and characterize such communities (Casey et al, 2021; Palomino‐Alvarez et al, 2021; Pearman et al, 2019, 2020). Here, we identified marine fungi Ascomycota, Basidiomycota, and red algae Rhodophyta as the main non‐metazoan eukaryote contributors to a tropical urban reef cryptobiome (Figure 2b; Appendix S1).…”
Section: Discussionmentioning
confidence: 99%
“…Since ARMS mimics the physical complexity of coral reefs, organisms that are dependent on reef cavities would likely also find ARMS suitable for inhabitation (Palomino‐Alvarez et al, 2021; Pearman et al, 2020; Plaisance et al, 2011; Zimmerman & Martin, 2004). Interestingly, we found that higher coral cover was associated with higher COI metazoan diversity though not with 18S metazoan diversity (Figure 4c), so it is possible that non‐invasive survey methods focused on conspicuous reef organisms have overlooked the “hidden majority” concealed within crevices that could drive these invertebrate richness patterns (Pearman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hydroids and bryozoans) can also be present. In ARMS, several food sources for heterobranch sea slugs are found, such as sponges, ascidians, bryozoans, hydroids and algae, because the structures are used as a hard substrate base (Palomino-Alvarez et al, 2021a, 2021b, thus increasing the possibility of finding specimens of different feeding habits.…”
Section: Discussionmentioning
confidence: 99%